Olfactory Dysfunction Predicts Disease Progression in Parkinson’s Disease: A Longitudinal Study - He, Runcheng; Zhao, Yuwen; He, Yan; Zhou, Yangjie; Yang, Jinxia; Zhou, Xiaoting; Zhu, Liping; Zhou, Xun; Liu, Zhenhua; Xu, Qian; Sun, Qiying; Tan, Jieqiong; et al. (Frontiers in Neuroscience, 2020)
Background and objective: Olfactory dysfunction (hyposmia) is an important non-motor symptom of Parkinson's disease (PD). To investigate the potential prognostic value of hyposmia as a marker for disease progression, we prospectively assessed clinical manifestations and longitudinal changes of hyposmic PD patients and normosmic ones. Methods: Olfactory function was evaluated with the Sniffin’ sticks in PD patients at baseline. 105 hyposmic PD patients and 59 normosmic PD patients were enrolled and followed up for 2 years. They were subsequently evaluated at baseline and during follow-up periods with neurological and neuropsychological assessments. Clinical manifestations and disease progressions were compared between hyposmic and normosmic patients. In addition, the relationship between disease progressions and olfactory function was analyzed. Results: Our study suggested that hyposmic PD patients and normosmic ones were similar in gender, age, education levels, age of onset, disease duration, and clinical features at baseline. Hyposmic PD patients exhibited more severe Unified Parkinson's Disease Rating Scale Part II-Ⅲ (UPDRS II-III) scores, higher levodopa equivalent dose (LED) needs, and poor Mini Mental State Examination (MMSE) score at follow-up visits, compared to normosmic PD patients. Hyposmia also showed greater rates in the increase of LED needs, improvement of UPDRS III score and deterioration of MMSE score. Both longitudinal improvement of UPDRS III score and decline of MMSE score were associated with the poorer odor identification. Conclusion: Our prospective study demonstrated that hyposmic PD patients showed a relatively worse clinical course compared with normosmic patients. Olfactory dysfunction is a useful predictor of disease progression.